2018
DOI: 10.1088/1361-6528/aa9d14
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band anti-reflective pore-like sub-wavelength surface nanostructures on sapphire for optical windows

Abstract: Compared with conventional anti-reflective film, an anti-reflective sub-wavelength surface structure provides an ideal choice for a sapphire optical window especially in harsh environments. However, it is still a challenge to obtain a sapphire anti-reflective surface microstructure because of its high hardness and chemical inertness. In this paper, combined with optical simulation, we proposed a facile method based on the anodic oxidation of aluminum film and following epitaxial annealing. Al thin film was dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Among various anti-reflective coatings, subwavelength structures [17][18][19][20][21][22] and gradient refractive layers [23][24][25][26][27] are currently widely used. Hong Li et al 28 prepared PiTG with a GRIN coating, revealing that compared to single refractive index (SRIN) coatings, the luminous efficiency of PiTG with the GRIN coating increased from 9.51% to 23.12%.…”
Section: Introductionmentioning
confidence: 99%
“…Among various anti-reflective coatings, subwavelength structures [17][18][19][20][21][22] and gradient refractive layers [23][24][25][26][27] are currently widely used. Hong Li et al 28 prepared PiTG with a GRIN coating, revealing that compared to single refractive index (SRIN) coatings, the luminous efficiency of PiTG with the GRIN coating increased from 9.51% to 23.12%.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-reflective (AR) treatments, such as thin-film coatings, suppress reflections by destructive interference along the propagating directional axis. Recent studies have demonstrated that random anti-reflective structured surfaces (rARSS) can be used as an alternative to thin film coatings, reducing Fresnel reflections in the visible and infrared (IR) [1][2][3][4]. Broadband response, high transmission across wide ranges of angle of incidence (AOI), and polarization insensitivity have also been reported [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that random antireflective structured surfaces (rARSS) can be used as an alternative to thin film coatings, reducing Fresnel reflections in the visible and the infrared (IR). [1][2][3][4][5][6][7][8] Broadband response, high transmission across wide ranges of angle of incidence (AOI), and polarization insensitivity have also been reported. 9,10 In general, the AR effects correlate with the density and depth of the nanostructures, simulating an effective medium gradient-index boundary profile, which reduces Fresnel reflectivity.…”
Section: Introductionmentioning
confidence: 99%